Institutional Communication as an Approach to Strengthening Governance in Organizations: An Analytical Study of the Relationship between the Quality of Institutional Communication and Governance Enhancement (The International Journal of Educational Sciences and Arts, 2026)
This study aims to examine the role of effective institutional communication in establishing and strengthening corporate governance in Saudi Arabia, particularly in light of contemporary efforts to improve the business environment, enhance institutional performance, and promote the principles of transparency, accountability, and participation in alignment with Saudi Vision 2030. The study is grounded in a central research problem: the implementation of governance principles within institutions cannot be achieved merely through regulations and administrative structures; rather, it requires an effective communication system that ensures the accurate, clear, and timely flow of information among management, employees, and stakeholders, while supporting trust-building and sound decision-making.The study adopts a descriptive-analytical approach by addressing the concept of institutional communication, its objectives, patterns, characteristics, and organizational functions, alongside an analysis of governance, its objectives, features, determinants, and implementation mechanisms. It also seeks to clarify the relationship between the quality of institutional communication and the enhancement of governance principles, particularly transparency, accountability, participation, institutional trust, crisis management, and the promotion of a governance-oriented organizational culture.The significance of this study lies in presenting a conceptual framework that connects institutional communication as a strategic management function with governance as an administrative and supervisory system aimed at improving performance, ensuring integrity, promoting fairness, and achieving sustainability. The study concludes that the quality of institutional communication is a fundamental condition for the successful implementation of governance. Effective communication contributes to reducing ambiguity, clarifying roles and responsibilities, enhancing employee participation, limiting rumors, and strengthening stakeholders’ trust in the institution. The study also emphasizes the importance of developing internal and external communication channels, investing in digital technologies, and improving communication skills among leaders and employees to ensure more effective application of governance principles within Saudi institutions.
Keywords: Institutional Communication; Corporate Governance; Institutional Governance; Transparency; Accountability; Institutional Participation; Organizational Trust; Internal Communication; Strategic Communication; Saudi Arabia